2016
DOI: 10.1021/acsami.6b10437
|View full text |Cite
|
Sign up to set email alerts
|

Human Dopamine Receptor-Conjugated Multidimensional Conducting Polymer Nanofiber Membrane for Dopamine Detection

Abstract: In the brain and central nervous system, dopamine plays a crucial role as a neurotransmitter or a local chemical messenger for interneuronal communication. Dopamine is associated with renal, hormonal, and cardiovascular systems. Additionally, dopamine dysfunction is known to cause serious illnesses, such as Parkinson's disease and Alzheimer's disease. Therefore, dopamine detection is essential for medical diagnosis and disease prevention and requires a novel strategy with high sensitivity and selectivity and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
68
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 45 publications
0
68
0
1
Order By: Relevance
“…The negatively increasing Vg led to an increasing Ids current, because a negative charge applied to the surface of an IgG/PPy NT changes the state of the intrinsic oxidation level in the PPy chains [34]. This result showed that the liquid-ion gated FET system has a clearly defined p-type transistor characteristic, with holes as the primary charge carrier [21]. In addition, the Ids-Vg characteristic depending on pH variation was observed in the range of pH 4.8, 7.4, and 8.8, and the charge density was changed by PPy NT surface charge variation ( Figure S4).…”
Section: Sensing Behavior Of Liquid-ion Gated Anti-cortisol Igg/ppy Nmentioning
confidence: 92%
See 1 more Smart Citation
“…The negatively increasing Vg led to an increasing Ids current, because a negative charge applied to the surface of an IgG/PPy NT changes the state of the intrinsic oxidation level in the PPy chains [34]. This result showed that the liquid-ion gated FET system has a clearly defined p-type transistor characteristic, with holes as the primary charge carrier [21]. In addition, the Ids-Vg characteristic depending on pH variation was observed in the range of pH 4.8, 7.4, and 8.8, and the charge density was changed by PPy NT surface charge variation ( Figure S4).…”
Section: Sensing Behavior Of Liquid-ion Gated Anti-cortisol Igg/ppy Nmentioning
confidence: 92%
“…The anti-cortisol IgG/PPy NT FET-type sensor was placed on the stage of a probe station (Model 4000, MS-Tech, Seoul, Korea), which was connected to the source meter [21]. Current-voltage (I-V) curves were measured by voltage scan (rate: 0.1 mV/s).…”
Section: Anti-cortisol Igg/ppy Nt/fet Based Cortisol Detectionmentioning
confidence: 99%
“…To enhance DA sensing performance, several sensor surface modification approaches were undertaken. Also, novel sensors utilizing nanoparticles [54], field-effect transistor (FET) [55], and conducting polymers [55,56] have been developed, but they are still unstable in the long term. Additionally, the surface functionalization of the sensor is complicated.…”
Section: Introductionmentioning
confidence: 99%
“…The 1D structure facilitates high charge‐carrier mobility along its long axis and allows facile functionalization . Therefore, 1D PPy was deemed suitable as a transducer substrate in an H 2 O 2 biosensor …”
Section: Introductionmentioning
confidence: 99%